Uplatnění matematických a statistických metod v řízení podniku - Udalova, Anna (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Cílem mé bakalářské práce je zhodnotit ekonomickou situaci podniku pomocí finanční analýzy. Teoretická část obsahuje popis metod a postupů finanční analýzy a princip časových řad a regresní analýzy ve statistice. Praktická část analyzuje současný stav prostřednictvím ekonomických ukazatelů, které následně ohodnotím pomocí statistických metod.

The main goal of this bachelor´s thesis is to evaluate the economic situation of the company through financial analysis. The theoretical part describes the methods and procedures of financial analysis and the principle of time series and regression analysis in statistics. The practical part analyzes the current situation using economic indicators, which I then evaluate and try using statistical methods.
Application of Mathematical and Statistical Methods in Company Management
Keywords: Analýza ekonomických ukazatelů; statistické metody; ekonomika podniku; finanční analýza; Analysis of economic indicators; statistical methods; economics; financial analysis